Facial Recognition Attendance System Using OpenCV implemented in Python - K, Nandhitha; M, Benisha (Journal of Ubiquitous Computing and Communication Technologies, 2024)
The Facial Recognition Attendance System is a sophisticated software solution that employs OpenCV and Python to automate the process of attendance tracking in real-time. Designed to replace outdated manual methods, this system utilizes state-of-the-art facial recognition technology to accurately identify individuals as they enter a monitored space. Upon detection and verification, the system records the individual’s attendance by logging their arrival time, thereby streamlining the attendance process. This method significantly enhances efficiency, reduces potential for error, and ensures a secure and contactless check-in experience. With its user-friendly interface and quick setup, the system is an ideal application for educational institutions, corporate offices, and public events that require reliable attendance management.